2009
DOI: 10.1038/tpj.2009.41
|View full text |Cite
|
Sign up to set email alerts
|

MDR1 (C3435T) polymorphism: relation to the risk of breast cancer and therapeutic outcome

Abstract: P-glycoprotein (PGP), the product of the MDR1 gene, is a transmembrane active efflux pump for a variety of carcinogens and cytostatics. It has been suggested that MDR1 polymorphisms contribute to the variability in cancer risk and therapeutic outcome. We examined the relevance of C3435T polymorphism in relation to breast cancer susceptibility, clinical and pathological characteristics of breast carcinoma, the therapeutic response and hematologic toxicities after anthracycline-based chemotherapy. A significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 28 publications
3
31
1
1
Order By: Relevance
“…The G2677T genetic variation results in an amino-acid change from an alanine residue to a serine in P-glycoprotein at position 893, while the C3435T SNP is silent. Due to the fact that the G2677T and C3435T SNPs are linked, our findings corroborate results from Cizmarikova et al [19] who found that patients with the 3435C/C genotype had a longer TTP and an enhanced therapeutic outcome after neoadjuvant anthracycline-based chemotherapy. In accordance, Turgut et al [20] showed a trend toward a shorter PFS for breast cancer patients with 3435T/T compared to heterozygous and wild-type patients.…”
Section: Discussionsupporting
confidence: 91%
“…The G2677T genetic variation results in an amino-acid change from an alanine residue to a serine in P-glycoprotein at position 893, while the C3435T SNP is silent. Due to the fact that the G2677T and C3435T SNPs are linked, our findings corroborate results from Cizmarikova et al [19] who found that patients with the 3435C/C genotype had a longer TTP and an enhanced therapeutic outcome after neoadjuvant anthracycline-based chemotherapy. In accordance, Turgut et al [20] showed a trend toward a shorter PFS for breast cancer patients with 3435T/T compared to heterozygous and wild-type patients.…”
Section: Discussionsupporting
confidence: 91%
“…Evaluation of MDR1 genotype and allele frequency (C3435T polymorphism) in patients with breast cancer (221 people) and healthy participants (113 people) showed that allele T is more often observed in the group of patients. Results of this trial confirmed the hypothesis that Tallele is usually associated with lower MDR1 expression and reduction in the P-gp function, thus maintaining worse protection of cells [11]. On the other hand, increase P-gp expression was revealed in the epileptics resistant to the conducted therapy.…”
supporting
confidence: 76%
“…This gene was found to be highly polymorphic and causes susceptibility to various disease and therapeutic clinical outcomes. A silent mutation in exon 26 namely C3435T has been reported to be associated with therapeutic outcomes in breast cancer treatment and other disease (17)(18)(19). Another allele G2677A/T in exon 21 had been shown to be associated with an amino acid change in Ala893Thr and Ala893Ser.…”
Section: Introductionmentioning
confidence: 99%